2003
DOI: 10.1046/j.1365-3180.2003.00343.x
|View full text |Cite
|
Sign up to set email alerts
|

Survival, germinability and fungal colonization of dimorphic achenes of the annual weedGalinsoga parvifloraburied in the soil

Abstract: Summary Galinsoga parviflora (Asteraceae) is a widespread annual weed that produces capitula containing both disc achenes with pappus and ray achenes without pappus. The latter are dispersed within a winged structure formed by capitulum bracts. We buried both achene types in an agricultural soil to be exhumed regularly to investigate whether they differed in survival, germinability and fungal colonization in the soil seedbank. Ray achenes remained viable longer than disc achenes, with different loss rates for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 21 publications
(34 reference statements)
0
16
0
2
Order By: Relevance
“…In the soil, fluctuations in temperature and moisture, and the action of microorganisms, may affect the integrity of the hard seed covers, although few papers have adequately documented this fact (Baskin and Baskin, 2000). The effect of microorganisms on seed covers, which has implications for seed viability and germination, has been variously reported as deleterious (Kremer and Schulte, 1989;Greenfield, 2000), beneficial (Pfeiffer, 1934;Gogue and Emino, 1979;Morpeth and Hall, 2000), and harmless (Espinosa-García et al, 2003;Schafer and Kotanen, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In the soil, fluctuations in temperature and moisture, and the action of microorganisms, may affect the integrity of the hard seed covers, although few papers have adequately documented this fact (Baskin and Baskin, 2000). The effect of microorganisms on seed covers, which has implications for seed viability and germination, has been variously reported as deleterious (Kremer and Schulte, 1989;Greenfield, 2000), beneficial (Pfeiffer, 1934;Gogue and Emino, 1979;Morpeth and Hall, 2000), and harmless (Espinosa-García et al, 2003;Schafer and Kotanen, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…This strategy is deployed by plants germinating from peripheral achenes to increase the pool of peripheral achenes, which are much less involved in species reproduction. Espinosa-García et al (2003) found that in the soil seed bank the peripheral achenes of G. parviflora remained viable for a longer period of time and lost their viability slower than the central achenes. This seems to be an important feature of the peripheral achenes of G. parviflora, because these peripheral diaspores thus can create a longer-lived seed bank than the central achenes.…”
Section: Different Strategies Of Reproductionmentioning
confidence: 97%
“…Peripheral achenes are without a pappus (or less frequently with an only vestigial one), and contain more protein and carbohydrates than central achenes. Central achenes have a pappus formed by a crown of scales (Espinosa-García et al, 2003;Rai and Tripathi, 1987). According to Rai and Tripathi (1987), peripheral achenes germinate faster and better than central ones.…”
Section: Introductionmentioning
confidence: 99%
“…(Venable et al 1987), Bidens odorata Cav., B. pilosa L. (Corkidi et al 1991;Pitty 1997) and Galinsoga parviflora Cav. (Espinosa-García et al 2003). It is usually an adaptation to varying germination conditions.…”
Section: Morphological Variabilitymentioning
confidence: 99%